LEARNING ISLAMIC RELIGIOUS EDUCATION THROUGH THE FLIPPED LEARNING MODEL TO ENHANCE STUDENT LEARNING MOTIVATION - Kulsum, Umi; Qodriyah, Khodijatul; Hamzah, Muh.; Rifa'i, Moh.; Rozi, Fathor (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to determine the impact of Flipped Learning on Islamic Religious Education learning and student learning motivation at Kertonegoro State Elementary School (SDN). The Flipped Learning method allows students to access learning materials before class sessions and allocates class time for interactive discussions and understanding concepts. This research involved teachers and students at SDN Kertonegoro in implementing Flipped Learning during a certain period. The results of the research show that Flipped Learning has a positive impact on Islamic Religious Education at SDN Kertonegoro. More intense interaction between teachers and students during class sessions increases the understanding of religious concepts and enhances student engagement in learning. In addition, Flipped Learning also contributes to increasing student learning motivation. Students show greater interest, more active participation, and a higher level of persistence in understanding religious teachings. Even though several technical obstacles were encountered, such as limited internet access, the long-term benefits of implementing Flipped Learning are believed to positively contribute to the quality of Islamic Religious Education learning at SDN Kertonegoro. The implications of this research provide a basis for the development of more adaptive and motivational learning strategies in the context of religious education at the elementary level. Hopefully, this research can contribute to a better understanding of the effectiveness of Flipped Learning in improving student learning and motivation. That this learning approach stimulates student curiosity and develops their independence in learning. Despite facing some technical hindrances, such as limited internet access in some areas, the long-term benefits of Flipped Learning are believed to contribute positively to the quality of Islamic Religious Education at SDN Kertonegoro. The implications of this research can assist in developing more adaptive and motivational learning strategies in the context of religious education at the elementary level.